2017
DOI: 10.17219/acem/63155
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of prosthetic needs of ESRD patients and the general population in Poland on the basis of the Eichner classification and teeth number: A brief, preliminary report

Abstract: Background. End-stage renal disease (ESRD) patients are considered as a group of high risk of oral cavity diseases. One of the determinants of alveolar bone loss and increased teeth mobility in ESRD patients might be the bone abnormalities associated with chronic kidney disease-mineral and bone disorder (CKD-MBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
4
0
3
Order By: Relevance
“…Wilczynska‐Borawska et al investigated the prosthetic requirements of patient with CKD and reported that approximately 70% of tested hemodialysis participants do not have a reconstructed masticatory function. Similar results were also reported by Miernik et al In another study, Sheiham et al stated that particularly nonstarch polysaccharides were consumed by people with 21 or more teeth. Nuwjack‐Raymer and Sheiham indicated that people with complete dentures have a poorer diet than people who have natural teeth.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Wilczynska‐Borawska et al investigated the prosthetic requirements of patient with CKD and reported that approximately 70% of tested hemodialysis participants do not have a reconstructed masticatory function. Similar results were also reported by Miernik et al In another study, Sheiham et al stated that particularly nonstarch polysaccharides were consumed by people with 21 or more teeth. Nuwjack‐Raymer and Sheiham indicated that people with complete dentures have a poorer diet than people who have natural teeth.…”
supporting
confidence: 86%
“…Tooth loss may induce the inappropriate selection, which is also estimated as a risk factor for malnutrition . Miernik et al compared the general health condition, number, and location of teeth in patients of CKD with the group of peers from general population and concluded that there was no statistical difference in prosthetic needs between two groups. In the present study, the distribution of the types of prostheses in patients who wore prosthesis (58.9%) were: 23.3% fixed dental prosthesis, 6.8% removable partial prosthesis, 16.4% total prosthesis, and 12.3% both fixed and removable prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miernik et al studied prosthetic treatment needs in patients with end-stage renal disease (ESRD), obtaining statistically insignificant results but indicating a very bad situation in terms of prosthetic treatment both in the study group and in the general population. 13 Thematically similar study was conducted by Castillo et al and Brito et al, but they also did not find a statistically significant difference between the group of patients on dialysis and the healthy controls. 14 In these studies, the authors searched for changes in the bone structure of the jaws, which could lead to disorders that accelerate tooth loss, unlike in the present study, in which the periodontal diseases factor is the link between cardiovascular diseases and premature loss of dentition.…”
Section: Discussionmentioning
confidence: 53%
“…Miernik i wsp. badali potrzeby leczenia protetycznego u pacjentów ze schyłkową niewydolnością nerek (SNN, End-stage renal diseasae (ESRD)) otrzymując nieistotne statystycznie wyniki, jednak wskazujące na bardzo złą sytuację pod względem leczenia protetycznego zarówno u grupy badanej, jak i populacji ogólnej 13 . Zbliżone tematycznie badania zostały przeprowadzone przez Castillo i wsp.…”
Section: Discussionunclassified